Evaluation of renal and hepatic functions in cattle with subclinical and clinical ketosis - Issi, Mustafa; Gul, Yusuf; Basbug, Onur (Tubitak Scientific & Technological Research Council Turkey, 2016)
The purpose of this study was to research the changes in renal and hepatic functions of high productive dairy cows diagnosed with subclinical and clinical ketosis. The material of the study consisted of 30 dairy cows of high milk production. Diagnosis of ketosis was made according to anamnesis, physical examination, urine ketone bodies, and serum beta-hydroxybutyric acid levels. The animals were divided according to their serum beta-hydroxybutyric acid levels into control, subclinical, and clinical ketosis groups, each of which included 10 cows. Serum glucose, urea, creatinine, total protein, aspartate amino transaminase (AST), and total bilirubin levels were determined with an automatic biochemistry analyzer using commercial test kits OptiumXceed; a handheld meter was used for the detection of serum beta-hydroxybutyric acid levels. The serum beta-hydroxybutyric acid levels were 450 +/- 0.05, 1310 +/- 0.03, and 3920 +/- 0.37 mmol/L in the control, subclinical, and clinical ketosis groups respectively, and there were significant differences among the 3 groups (P < 0.001). The intergroup significant differences of some biochemical parameters (glucose, total protein, urea, creatinine, AST, and total bilirubin) were determined. New studies must be conducted to determine the glomerulus filtration rate in animals (particularly those with subclinical ketosis) with normal serum creatinine concentrations and suspected kidney disease.
Keywords: Ketosis; dairy cow; beta-hydroxybutyric acid; biochemical parameters